Biochemical and molecular characterisation of njavara types of rice (Oryza sativa L.) - Sanal Kumar P (Department of Plant Breeding and Genetics, College of Horticulture, 2005)
Characterisation and evaluation of Njavara types of rice (Oryza sativa L.) was under taken in the Department of Plant Breeding and Genetics and Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, Vellanikkara during 2001 - 2005 with the aim to characterise the Njavara genotypes based on morphological, biochemical and molecular characteristics, to evaluate its nutritional qualities and to analyse the stability of quantitative and nutritional traits.